Battery thermal performance oriented all-electric ship microgrid modeling, operation and energy management scheduling. (April 2022) - Hein, Kyaw; Murali, Rakesh; Xu, Yan; Aditya, Venkataraman; Gupta, Amit Kumar
Abstract: Energy storage system (ESS) integrated all-electric ship (AES) is gaining popularity as it renders higher efficiency and emission reduction. Being an isolated system, generation and storage capabilities are limited, and hence network losses, mechanical and electrical load estimation must be modeled accurately to establish a reliable operation strategy. Thus, the presented work proposes a modeling and operation strategy based on the propulsion architecture, mission profile, operation modes, and thermal performance of ESS. The following aspects are incorporated to improve the accuracy. (1) Electrical load demand, and loss modeling at the generation and load side; (2) energy management system (EMS) for optimal energy dispatch; (3) and experiment-based ESS electrical characterization and cooling designs for the thermal management system. Firstly, mathematical models of electrical components and mechanical propulsion units are used to establish the net electrical load demand from the propulsion and auxiliary units. The parameters obtained from load models are used in EMS energy dispatch to minimize the fuel and thermal-performance-dependent ESS operation costs. Finally, generation side losses are included in the final dispatch to meet the net electrical load demand of the vessel. Based on electrical parameters from test setup and different cooling designs, a battery management system is modeled to estimate the ESS pouch's temperature profile that is used as an operational constraint of EMS to discourage ESS from operating at high temperatures. Simulation results indicate the impact of AES propulsion architecture and ESS thermal performance on its operation. The results suggest the strong influences of mission profile and operation modes in designing a realistic operation schedule for the actual implementation. Highlights: Unified system-level model with detailed electrical and thermal modeling of an all-electric ship power system is proposed. It considers propulsion architecture, shore-connection, power conversion units, and energy storage. Battery pouch's RC characterization is done based on experimental data. The proposed second-order equivalent RC simulation model of the battery pouch is verified. Energy storage thermal performance with various cooling designs such as air and liquid are investigated. Task-dependent operation logic-based energy management optimization is proposed. It reduces fuel consumption and temperature-dependent energy storage operation cost. Sensitivity analysis of Levelized energy storage cost is carried out to map the solution space between the fuel consumption and energy storage operation cost.